PHBS Elementary School Children through CTPS in an Effort to Prevent the Risk of Covid-19 Transmission - Santi, Devi Nuraini; Bakti, Alam (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Covid-19 is an outbreak of a new disease that already exists and has become a pandemic. This disease is caused by a new type of corona virus named SARS-CoV-2. During the global pandemic, one of the cheapest, easiest and most important ways to prevent the spread of the virus is to wash your hands frequently with soap and water. The most prominent problem at UPT SD Negeri 064023, Kelurahan Kemenangan Tani, Medan Tuntung District, Medan is the low level of education about the importance of washing hands with soap and the unavailability of facilities for students to wash their hands with soap in running water. This service provides facilities for washing hands with soap in running water and education about breaking the chain of transmission of COVID-19 and how to wash hands with soap properly. Educational activities in elementary schools are carried out through teachers and staff in elementary schools because school children are still learning from home. They are the ones who will deliver the education to students through online lessons or when the children return to study at school. The provision of 2 handwashing basins in schools is very useful to be used as a forum for health protocol actions to break the chain of covid transmission 19. The school principal is grateful and states that he is ready to cooperate for further community service activities